Nanoclay Recent Advances, New Perspectives and Applications - Oueslati, Walid (IntechOpen, 2022)
Nanoclays, currently regarded as nanomaterials with sustainable characteristics, have a variety of intriguing properties. Clays come in a wide variety of nanoscale morphologies and are chemically made up of hydrated aluminum silicates with varying amounts of additional elements like magnesium, iron, calcium, and potassium. Given their properties and accessibility in a variety of nanoscale morphologies, nanoclays are well suited for a broad range of possible uses. To create nanocomposite materials with specific characteristics and particular functionalities, composites based on polymers and clay nanoparticles have been thoroughly investigated. Recent research has demonstrated the use of polymer/nanoclay systems in the antibacterial coating, smart food packaging, drug delivery systems, tissue engineering, reinforced bioplastics, and flame-retardant materials. However, further study is still required to clarify their structure-property relationships. Hybrid organic/inorganic clays generate a wide number of perspectives, nanoarchitectures and materials. In general, the utilization of nanoclays can remove the typical cost barrier associated with nanotechnologies and provide new, sustainable pathways. The contributions that describe recent research in nanoclay science for technological applications are collected in this edited volume.